A Review of Recent Skills Required as Engineering Project Managers - Othman, Mohd Hilmi; Mohd Ariff Sulor; Mohammed Haidar (Journal of Advanced Mechanical Engineering Applications, 2022)
Most of the project engineers are presumed to be promoted as the project manager after certain period of services. However, they are required to attain certain qualities in order to manage the project effectively. Hence, this paper summarised several recent skills required for an engineering project managers. This paper relates the role of the engineering project manager with the skills required to accomplish the managerial jobs. The skills are divided into six categories, which are conceptual skills, human skills, political skills, technical skills, negotiating skills and budgeting skills. Each of these skills were discussed with several examples as the reference. It was believed that these skills are needed for the project managers to boost up the management performance, in the real engineering project field, and the findings of this paper could become the appropriate guidelines for the young engineers as the motivation to climb up the promotional ladder as some successful project managers.